Taxonomic Contributions to the Lithosiini (Lepidoptera: Erebidae: Arctiinae) from India: Description of Two New Species and Seven New Species Records - Singh, Santosh; Bhattacharya, Srishti; Singh, Navneet; Kirti, Jagbir Singh (Zootaxa, 2026)
Two new species of lichen moths (Erebidae: Arctiinae: Lithosiini) are described from India: Caulocera hollowayi sp. nov. from Sikkim and Asura buxa sp. nov. from West Bengal. In addition, seven species records are newly reported and re-described: Fangeilema amoena Volynkin & Saldaitis, 2023 from West Bengal, Collita serva (Walker, 1854) from Arunachal Pradesh, Manulea complana (Linnaeus, 1758) from Jammu & Kashmir, Tarika spitzeri Volynkin & Černý, 2025 and Tarika kachina Volynkin & Černý, 2025 from Arunachal Pradesh, Tarika pinratnai Volynkin & Černý, 2025 from Mizoram, and Macrobrochis albovenosa Černý, 2009 from West Bengal.